Taxonomy and phylogeny of European Gymnopus subsection Levipedes (Basidiomycota, Omphalotaceae) - Antonín, V; Sedlák, P; Tomšovský, M (Persoonia, 2013)
The systematic integrity of European Gymnopus subsect. Levipedes is verified based on anatomic-morphological characters with support from DNA sequences of ITS and translation elongation factor 1-alpha genes. Seven species (G. alpinus, G. aquosus, G. dryophilus - including var. lanipes, G. erythropus, G. fagiphilus, G. hybridus, and G. ocior) belonging to this subsection are included. We clarify the concepts of G. dryophilus and G. ocior, which were occasionally confused in older literature. Due to unavailability of previously selected neotype of G. dryophilus the substitute neotype specimen is selected. Gymnopus dryophilus var. lanipes is confirmed as a variety; no important differences from nominotypical variability were detected. All discriminative characters used for identification of these species are discussed in detail. An identification key is also provided.
Keywords: nomenclature; translation elongation factor 1-alpha; ITS; neotype